西西的推广(加边问题)

陈洪葛 posted @ May 11, 2014 11:01:27 AM in 数学分析 , 1049 阅读

问题:正数列$\{a_{n}\}$满足$\displaystyle a_{n}\left(\sum_{i=1}^{n}a_{i}^{p}\right)=1$,且$p>-1$是已知常数,求$A,B$,使得$A,B$ 满足
\[ \lim_{n\to\infty}\frac{n}{\ln{n}}(A-na_{n}^{p+1})=B \]
解:设$S_{n}=\sum_{i=1}^{n}a_{i}^{p}$
容易证明
\[ \lim_{n\to\infty}{a_{n}}=0,\lim_{n\to\infty}S_{n}=+\infty \]
由O.Stolz定理得到
\[ \lim_{n\to\infty}na_{n}^{p+1}=\lim_{n\to\infty}\frac{1}{\frac{1}{a_{n+1}^{p+1}}-\frac{1}{a_{n}^{p}}}=\lim_{n\to\infty}\frac{1}{S_{n+1}^{p+1}-S_{n}^{p}} \]

\begin{align*}
 S_{n+1}^{p+1}-S_{n}^{p+1}&=S_{n+1}^{p+1}-(S_{n+1}-a_{n+1}^{p})^{p+1}\\
&=S_{n+1}-\sum_{k=0}^{p+1}C_{p+1}^{k}(-1)^{k}S_{n+1}^{p+1-k}\cdot a_{n+1}^{pk}\\
&=(p+1)S_{n+1}a_{n+1}-\frac{(p+1)p}{2!}S_{n+1}^{p-1}a_{n+1}^{2p}+\cdots\\
&=(p+1)+o(1) \qquad (n\to+\infty)
\end{align*}
所以
\[ A=\frac{1}{p+1} \]
同时有
\[ (p+1)a_{n}^{p+1}\sim \frac{1}{n} \]
这时
\[ \lim_{n\to\infty}\frac{n}{\ln{n}}(A-na_{n}^{p+1})=\lim_{n\to\infty}na_{n}^{p+1}\cdot\lim_{n\to\infty}\frac{A\cdot S_{n}^{p+1}-n}{\ln{n}}\]
又有O.Stolz定理
\begin{align*}
\lim_{n\to\infty}\frac{A\cdot S_{n}^{p+1}-n}{\ln{n}}&=\lim_{n\to\infty}\frac{A(S_{n+1}^{p+1}-S_{n}^{p})-1}{\ln\left(1+\frac{1}{n}\right)}\\
&=\lim_{n\to\infty}\dfrac{\frac{1}{p+1}((p+1)-\frac{(p+1)p}{2}S_{n+1}^{p-1}a_{n}^{2p}+\cdots)}{\frac{1}{n}}\\
&=\lim_{n\to\infty}\dfrac{-\frac{p}{2}S_{n+1}^{p-1}a_{n+1}^{2p}+o(S_{n+1}^{p-1}a_{n+1}^{2p})}{(p+1)a_{n+1}^{p+1}}\\
&=-\frac{p}{2(p+1)}
\end{align*}
所以
\[ B=-\frac{p}{2(p+1)^2} \]

Avatar_small
陈洪葛 说:
2014年6月22日 10:09

这个暂时有点问题,待修复


登录 *


loading captcha image...
(输入验证码)
or Ctrl+Enter